Institutional investors' horizons and corporate employment decisions - Ghaly, Mohamed; Dang, Viet Anh; Stathopoulos, Konstantinos (Journal of Corporate Finance, 2020)
Monitoring by long-term investors should reduce agency conflicts in firms' labor investment choices. Consistent with this argument, we find that abnormal net hiring, measured as the absolute deviation from optimal net hiring predicted by economic fundamentals, decreases in the presence of institutional investors with longer investment horizons. Firms dominated by long-term shareholders reduce both over-investment (over-hiring and under-firing) and under-investment (under-hiring) in employees. The monitoring role of long-term investors is stronger for firms facing higher labor adjustment costs both in absolute terms and relative to capital adjustment costs, and those for which human capital is regarded as more important. The effect is also more pronounced for firms that have stronger incentives and/or more opportunities to deviate from expected net hiring. We address endogeneity concerns by exploiting exogenous changes to long-term institutional ownership resulting from annual reconstitutions of the Russell indexes.